2019
DOI: 10.1177/2325967119s00379
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic debridement versus refixation of the acetabular labrum associated with femoroacetabular impingement: Updated mean 7 year follow-up

Abstract: Objectives: The acetabular labrum provides sealing function and a degree of hip joint stability. Previous early (16 month) and mid-term (mean 3.5 years) follow-up of this cohort reported better patient related outcome measures in the refixation group. To update the results of labral refixation versus focal labral excision/debridement in a cohort of patients who underwent arthroscopic correction of femoroacetabular impingement (FAI). Methods: We reported patients who underwent labral debridement/focal labral ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(121 citation statements)
references
References 0 publications
5
113
1
2
Order By: Relevance
“…The outcomes of this study are comparable to previously reported studies with significant functional improvement as well as high return to sport/activity. [4][5][6][7]13,14,[18][19][20] This studies results suggest that accelerated weight bearing and early ROM can assist in attaining positive outcomes in terms of early improvements in rehabilitation while minimizing potential adverse effects, a concept that is supported in the literature. 18 Likewise, there were no observed failures related to early weight bearing to include catastrophic failures such as femoral neck fracture or hip instability.…”
Section: Discussionmentioning
confidence: 61%
“…The outcomes of this study are comparable to previously reported studies with significant functional improvement as well as high return to sport/activity. [4][5][6][7]13,14,[18][19][20] This studies results suggest that accelerated weight bearing and early ROM can assist in attaining positive outcomes in terms of early improvements in rehabilitation while minimizing potential adverse effects, a concept that is supported in the literature. 18 Likewise, there were no observed failures related to early weight bearing to include catastrophic failures such as femoral neck fracture or hip instability.…”
Section: Discussionmentioning
confidence: 61%
“…The studies that compared labral resection with labral refixation have pointed significantly better radiological outcomes with fewer indications for THA when the labrum was preserved and fixed [26, 27, 33]. Redmond et al [13] found no differences in revision surgeries in patients treated with acetabuloplasty with and without labral detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, although labral preservation may be important for improving hip symptoms, 7 it is unclear whether this is because preservation surgery was biased to a population with isolated, rather than whole joint disease. There is some evidence to support this possibility, as factors such as degeneration, complex tears, calcification and ossification reduce the potential for labral repair and debridement is necessary 19 . Labral debridement may, therefore, be a marker of more widespread hip degeneration, which is a worse prognosis.…”
Section: Hip Arthroscopy For Femoroacetabular Impingement: Lessons Frmentioning
confidence: 99%
“…There is some evidence to support this possibility, as factors such as degeneration, complex tears, calcification and ossification reduce the potential for labral repair and debridement is necessary. 19 Labral debridement may, therefore, be a marker of more widespread hip degeneration, which is a worse prognosis.…”
Section: Rationale For Non-surgical Therapy In Femoroacetabular Impinmentioning
confidence: 99%